Targeting WEE1 and asciminib suppresses ABL-tyrosine kinase inhibitor-resistant chronic myeloid leukemia cells - Seiichi Okabe; Mitsuru Moriyama; Akihiko Gotoh; Daigo Akahane (Discover Oncology)
Abstract Background Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm characterized by the uncontrolled proliferation of white blood cells. Tyrosine kinase inhibitors (TKIs) are the standard treatment; however, resistance to BCR::ABL1 mutations remains challenging. WEE1, a checkpoint kinase involved in mitosis and DNA repair, is a potential therapeutic target for CML treatment. Methods Ponatinib-resistant CML cells were screened to identify candidates for overcoming drug resistance. The efficacy of the ABL TKI asciminib and the WEE1 inhibitor MK-1775 was evaluated using proliferation and colony formation assays. Public database analysis (GSE100026) assessed WEE1/PKMYT1 expression in CML. Results In vitro screening identified MK-1775 as a promising therapeutic candidate. WEE1/PKMYT1 expression was elevated in CML cells compared to healthy cells. Both asciminib and MK-1775 inhibited CML cell proliferation after 72 h, with enhanced cytotoxicity when combined. Co-treatment reduced colony formation and induced G2/M arrest, whereas an increase in the sub-G1 cell population indicated apoptosis. Furthermore, the combination treatment disrupted the mitochondrial membrane potential. Conclusions The combination of asciminib and WEE1 inhibition demonstrated greater efficacy than either drug alone, suggesting a novel therapeutic strategy for treating CML. These findings provide insights into overcoming TKI resistance and highlight a promising approach for future clinical applications.